Mathematical modeling of reversible deactivation radical polymerization - Saldívar-Guerra, Enrique (Current opinion in chemical engineering, 2024)
Since its creation and diversification 30 years ago, reversible deactivation radical polymerization (RDRP) has gained tremendous relevance as a powerful and versatile set of techniques for the robust synthesis of precise polymer architectures for advanced applications. In parallel, mathematical models for the polymerization kinetics, molar mass distributions, and copolymer characteristics have rapidly developed and gained sophistication and detail. The aim of this review is to provide a summary of the most important modeling techniques used in RDRP and a brief description of the most recent literature on the subject, highlighting the most relevant issues and subjects addressed in these works.